Characterization of nanosized NiZn ferrite powders synthesized by an autocombustion method - Deka, Sasanka; Joy, Pattayil Alias (Materials Chemistry and Physics, 2006)
Nanocrystalline Ni0.5Zn0.5Fe2O4 with average particle size of similar to 9 nm has been synthesized by an autocombustion method and characterized by powder XRD, TEM and room temperature magnetic measurements. High room temperature magnetization comparable to that of the bulk material is obtained for the nanosized powders annealed at 800 degrees C, with a maximum particle size of similar to 54 nm. The results show that optimum properties can be achieved for NiZn ferrite powders synthesized by the present autocombustion method and processed at relatively lower temperatures. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Oxides

Low temperature synthesis of nanocrystalline lithium ferrite by a modified citrate gel precursor method - Verma, Seema; Joy, Pattayil Alias (Materials Research Bulletin, 2008)
Single phase nanocrystalline lithium ferrite is synthesized by a modified citrate gel precursor technique. Ferrite nanoparticles of average size of 8 nm, obtained after calcination of the citrate gel Made by the usual method at 450 degrees C, show superparamagnetic behavior. However, small amounts of alpha-Fe(2)O(3) is formed as an impurity phase clue to the initial formation of some gamma-Fe(2)O(3) phase. Oil the other hand, when the pH of the mixed Solution is increased to 7 after the addition of ammonia Solution, a lower calcination temperature of 200 degrees C is sufficient for the formation of single phase lithium ferrite nanoparticles of size 30 nm. No impurity phases are detected when the nanocrystalline powders arc calcined at higher temperatures. The magnetic properties of the ferrite nanoparticles of different sizes obtained by calcining the powders at different temperatures are studied. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Nanostructures; Oxides

Ferromagnetic properties of glucose coated Cu2O nanoparticles - Mahajan, Mangesh B.; Pavan, M. S.; Joy, Pattayil Alias (Solid State Communications, 2009)
Magnetic properties of glucose coated cuprous oxide nanoparticles of different sizes have been studied. Unlike bulk Cu2O, which shows diamagnetic behavior, the nanoparticles show superparamagnetic behavior. A superparamagnetic blocking temperature of 21 K is observed for 5 nm particles. A magnetic hysteresis loop with a coercivity of 406 Oe is observed for these particles at 5 K. The magnetization and the coercivity increase with decreasing particle size. The superparamagnetic behavior, along with the increase in magnetization and coercivity with decreasing particle size, is due to the enhanced surface contributions to the magnetism. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Cuprous oxide; magnetic properties; Nanoparticles

Simple chemical co-precipitation/calcination route for the synthesis of simulated synroc-B and synroc-C powders - Potdar, H. S.; Vijayanand, S.; Mohaideen, Kamal Khaja; Patil, K. R.; Joy, Pattayil Alias; Madhavan, R. Raja; Kutty, K. V. G.; Ambashta, Ritu D.; Wattal, P. K. (Materials Chemistry and Physics, 2010)
A simple chemical co-precipitation/calcination route was developed for the synthesis of simulated synroc-B and synroc-C powders using mostly nitrate salts as starting chemicals and 20% ammonia solution as precipitant. In this route, a mixed solution containing Al-nitrate, Ca-nitrate, Ba-nitrate, zirconyl nitrate and titanyl nitrate in the molar proportion required for synroc-B is added to dilute ammonia solution to precipitate these cations in the form of their hydroxides at room temperature by maintaining pH approximate to 10.5 during precipitation. Formation of a major fluorite phase with minor amounts of anatase, rutile and hollandite phases is observed in the powder obtained after calcination in air at 750 degrees C. Multiphase crystalline synroc-B matrix containing hollandite, perovskite, zirconolite, and rutile phases is obtained after sintering the heat treated powder in the form of pellets at 1230 degrees C for 4h in air. Similarly, pure synroc-C phases with 14 and 20% simulated waste loadings were synthesized following the same synthesis protocol. These pre-treated powders with a high surface area of similar to 25 m(2) g(-1) gave sintered ceramics having density of similar to 90% for 14 and 20% waste loadings. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Oxides; Sintering

Structural, magnetic and mossbauer spectral studies of nanocrystalline Ni0.5Zn0.5Fe2O4 ferrite powders - Verma, Seema; Joy, Pattayil Alias; Kurian, Sajith (Journal of Alloys and Compounds, 2011)
Nanocrystalline Ni0.5Zn0.5Fe2O4 powders, synthesized by a combustion method are investigated by X-ray diffraction, vibrating sample magnetometry and Mossbauer spectroscopic techniques. We adopt a strategy to systematically control the particle sizes between 4 and 45 nm simply by changing the elemental stoichiometric coefficient, Phi(e), of the combustion mixture. Curie temperature of the superparamagnetic particles of size 4 nm is higher than that of the bulk particles. Interestingly, bigger particles (45 nm) show a comparable room temperature saturation magnetization and exceptionally very high Curie temperature of 833 K, when compared to that of the bulk Ni0.5Zn0.5Fe2O4 material (563 K). (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Chemical synthesis; Magnetisation; Mossbauer spectroscopy; Nanostructured materials